PENGARUH MODEL PEMBELAJARAN QUANTUM TEACHING PADA BENTUK PENILAIAN PORTOFOLIO BERBASIS KELAS DAN JENIS SEKOLAH TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - Hartini, Sri (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2017)
The objective of the present research is to determine whether there is or not the effect of Quantum Teaching learning model on class- and school type-based portfolio assessment mode and its interaction effect on the mathematical problem solving ability of students in both elementary schools and madrasah ibtidaiyahs in Indramayu.The research method used was an experimental method with a 2x2 factorial design. Learning method, assessment mode, and school type were the treatment variables, and mathematical problem solving ability was respond variable. The research sample was grade-V students of SDs Karang Anyar I & II and grade-V students of MI PUI and Al-Irsyad of Indramayu selected by a cluster random sampling. The analysis technique used was two-way ANAVA to test both main effect and interaction effect. From the research result it was concluded that (1) the elementary school student group treated with Quantum Teaching learning model with class-based portfolio assessment mode was more effective in enhancing mathematical problem solving ability than madrasah ibtidaiyah group, (2) the students group treated with Quantum Teaching learning model with display portfolio assessment mode was more effective in enhancing mathematical problem solving ability than the student group treated with document portfolio assessment mode. It was suggested that Quantum Teaching learning model with a display portfolio assessment mode should be made as a learning model prioritized in mathematics learning in schools.